2021
DOI: 10.1007/s11469-021-00599-8
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Self-reported Inhibitory Control, Stress, and Alcohol (Mis)use During the First Wave of the COVID-19 Pandemic in the UK: a National Cross-sectional Study Utilising Data From Four Birth Cohorts

Abstract: We explored (1) self-reported changes in alcohol use during the pandemic in the UK and (2) the extent to which self-reported inhibitory control and/or stress were associated with any change in drinking behaviour. We used a UK-based cross-sectional online survey administered to four nationally representative birth cohorts (N = 13,453). A significant minority of 30- (29.08%) and 50-year-olds (26.67%) reported drinking more, and between 32.23 and 45.02% of respondents reported feeling more stressed depending on t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…It’s well-documented that heightened levels of anxiety and stress, as experienced during the COVID-19 pandemic, can detrimentally affect executive inhibitory control ( Clay et al, 2023 ). Chronic stress is often associated with structural and functional alterations in critical brain regions like the prefrontal cortex and anterior cingulate cortex, pivotal for executive function and inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…It’s well-documented that heightened levels of anxiety and stress, as experienced during the COVID-19 pandemic, can detrimentally affect executive inhibitory control ( Clay et al, 2023 ). Chronic stress is often associated with structural and functional alterations in critical brain regions like the prefrontal cortex and anterior cingulate cortex, pivotal for executive function and inhibitory control.…”
Section: Discussionmentioning
confidence: 99%
“…These potential differential impacts of the pandemic on alcohol use should be investigated. In addition, it is crucial to assess people who are younger in age (and therefore who were more likely to consume alcohol on‐site prepandemic compared to people who are older in age and were more likely to consume alcohol off‐site prepandemic), as a study conducted in the United Kingdom found individuals who were thirty years old (millennials) and 50 years old (Generation X) were more likely to report increased drinking compared to 19‐year‐olds (Generation Z) and 62‐year‐olds (Baby Boomer generation) (Clay et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our regressions detected socio‐economic effects at both ends of the spectrum; drinkers with the most education as well as those with the most household economic burdens from COVID‐19 had higher odds of having alcohol delivered. Stress has played a key role in alcohol consumption during the pandemic [35–37], and this may have encouraged the use of delivery services among those hit hardest economically by the pandemic. Delivery service utilisation by those with COVID‐19 economic burdens may lead to socioeconomic disparities because drinkers with a higher educational advantage may have access to resources that will allow them to mitigate or offset adverse effects of their consumption [38].…”
Section: Discussionmentioning
confidence: 99%